PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Bagian Produksi Cokelat PT. Pusan Manis Mulia Tangerang) - Teguh Syah Putra; Agus Hermani; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2013)
The aim of this study was to determine the effect of leadership style variable and employee environment on the performance of the chocolate production of PT. Pusan Manis Mulia Tangerang. The population of this study were 400 employees of chocolate production division of PT. Pusan Manis Mulia Tangerang, slovin samples formula was used resulted 80 people for sample and  the spreading using the method of Nonprobability Sampling (Purposive Sampling).  Likert scale was used as measurement scale. Simple linear regression test and regression test with SPSS 15.0 program were used in the data analysis. From the results of data analysis known that in the category of Leadership Style 62.5 percent of the respondence said that it was good. Employee Environment categories 72.5 percent of the respondence said it was good.  Category of employee performance most of of the respondence about 68.75 percent said it was good. Leadership Style variables affect the performance of employees by 73.2 percent. Employee Environment variable effect on employee performance by 75.3 percent. Taken together Leadership Style and Employee Environment of Employee Performance by 75.9 percent. This means the better the Leadership Style and Employee Environment is expected that the better the performance. Based on these results the management of PT. Pusan Manis Mulia Tangerang needs to consider the application of Leadership Style by head division of chocolate production. Companies need to increase the quality of employee environment given to employee.